PERAN PARA PENATUA DI GEREJA TERHADAP PERTUMBUHAN ROHANI PEMUDA DI GKPI JK BATU AJI LAMA BATAM - Rut Melisa Martalena. H; Epafras Mujono; Lie Agan (Universitas Kristen Immanuel, 2024)
Nowadays, there are church elders who do not carry out their service duties properly. Such as the fact found in this study that there are church elders who often miss their schedule to deliver the Word of God during youth fellowship services. This apparently has an impact on youth who feel they are not experiencing growth in their spiritual life. Therefore, this study aims to explain how the role of elders in the church towards the spiritual growth of youth in GKPI JK Batu Aji Lama Batam. In the discussion of this research, the researcher used the GKPI almanac book and books about spiritual growth from several sources as the theory. The type of research used is qualitative research. With several data collection techniques such as observation, interview and questionnaire distribution. The data that has been collected is then analyzed using the Miles and Huberman model analysis technique. In this study, it was found that the church elders in carrying out their role to grow the spirituality of the youth had gone well, but there were several things that needed to be evaluated by the elders. Interestingly, in this study it turned out to recognize the existence of other factors that were not the focus of this study which contributed to the spiritual growth of the youth. For this reason, through this study, the researcher suggests other researchers to conduct further research with the aim of discussing these other factors in more depth.